2007
DOI: 10.1038/nature06146
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Dnmt3a bound to Dnmt3L suggests a model for de novo DNA methylation

Abstract: Genetic imprinting, found in flowering plants and placental mammals, uses DNA methylation to yield gene expression that is dependent on the parent of origin 1 . DNA methyltransferase 3a (Dnmt3a) and its regulatory factor, DNA methyltransferase 3-like protein (Dnmt3L), are both required for the de novo DNA methylation of imprinted genes in mammalian germ cells. Dnmt3L interacts specifically with unmethylated lysine 4 of histone H3 through its amino-terminal PHD (plant homeodomain)-like domain 2 . Here we show, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
751
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(785 citation statements)
references
References 30 publications
31
751
2
1
Order By: Relevance
“…3,4 The R882 residue resides in the dimerization domain of DNMT3A and is important for enzymatic activity. 25 Mutation of R882 decreases enzyme activity by 50%, leading to suppressed DNA methylation and aberrant gene expression. 2 Seven mutations detected in our study (p.C306X, p.C330X, p.I407S, p.I407T, p.C583Y, p.N710S, and p.W893R) have not been reported previously, thus adding to the growing list of DNMT3A mutations in AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The R882 residue resides in the dimerization domain of DNMT3A and is important for enzymatic activity. 25 Mutation of R882 decreases enzyme activity by 50%, leading to suppressed DNA methylation and aberrant gene expression. 2 Seven mutations detected in our study (p.C306X, p.C330X, p.I407S, p.I407T, p.C583Y, p.N710S, and p.W893R) have not been reported previously, thus adding to the growing list of DNMT3A mutations in AML.…”
Section: Discussionmentioning
confidence: 99%
“…24 The PDB structure files used for modeling studies were from structures reported previously for DNMT3A (PDB codes 2QRV, 3A1A, and 3LLR). 25 …”
Section: Modeling Of Structural and Stability Changes Induced By Dnmtmentioning
confidence: 99%
“…Factors and features identified so far as specificity determinants for imprinting in oocytes include: (1) transcription traversing ICRs (Figure 1), 26 (2) unmethylated lysine-4 of histone H3 (H3K4), 27 (3) 10-bp CpG spacing, 28 (4) a histone H3K4 demethylase Kdm1b (Figure 1) 29 and (5) a Krüppel-associated box (KRAB) zinc finger protein Zfp57 (Figure 1). 30 Among these, the first three seem common to all oocyte-methylated ICRs and could be prerequisites for imprint establishment.…”
mentioning
confidence: 99%
“…Transcription through ICRs may make the chromatin more accessible by the Dnmt3a-Dnmt3L complex; 26 unmethylated, but not methylated, H3K4 is the high-affinity binding target of Dnmt3L; 27 two CpG sites located 10-bp apart fit very well with the catalytic centers of the heterotetrameric Dnmt3a-Dnmt3L complex. 28 However, these features can be found elsewhere in the genome and are not specific to ICRs. By contrast, Kdm1b acts only on a subset of ICRs (for example, ICRs at Mest, Grb10, Plagl1 and Impact loci), 29 although demethylation of H3K4 by this enzyme is consistent with the preference of Dnmt3L for unmethylated H3K4.…”
mentioning
confidence: 99%
“…Dnmt3a can also function as a DNA demethylase [54]. Dnmt3L is a catalytically inactive homologue of Dnmt3a and Dnmt3b that functions as an essential regulatory cofactor for tetrameric complex assembly [55].…”
Section: Mammalian Dnmts In the Central Nervous Systemmentioning
confidence: 99%